A bibliometric analysis on delirium in intensive care unit from 2013–2023 - Ma, Xin; Wu, Qingya; Ran, Yue; Cao, Xueqin; Zheng, Hua (Frontiers in Neurology, 2025)
BackgroundDelirium is a common manifestation of acute brain dysfunction among patients in the Intensive Care Unit (ICU), afflicting an estimated 30–35% of this vulnerable population. The prevalence of delirium in ICU settings has catalyzed a surge in academic interest, as evidenced by a growing body of literature on the subject. This study seeks to synthesize the progress in understanding ICU delirium through a bibliometric analysis.MethodsWe conducted a comprehensive search of the Web of Science Core (WOS) Collection database for literature on ICU delirium, focusing on studies published between 2013 and 2023. Our analysis utilized two bibliometric software tools, Citespace and VOSviewer, to scrutinize the data across various dimensions, including country contributions, authorship patterns, publishing journals, key thematic terms, and other pertinent metrics, with the aim of identifying emerging trends in the field.ResultsOur search yielded a total of 1,178 publications on ICU delirium within the WOS database from January 2013 to June 2023. The United States emerged as the leading contributor in terms of published articles, with Ely, E. Wesley being the most prolific author, having published 85 articles, and “Critical Care Medicine” as the journal with the highest number of publications, totaling 105. The application of literature clustering and keyword analysis revealed that future research is poised to delve deeper into areas such as pediatric delirium, risk factors, and the development of preventive and therapeutic strategies.ConclusionThis study employs bibliometric analysis to provide a multifaceted overview of the ICU delirium research landscape over the past decade. By examining the topic from various perspectives, we have not only mapped the current state of ICU delirium research but also illuminated potential avenues for future inquiry and areas of emphasis.